RESEARCH OF EASTERN AND WESTERN SCHOLARS ON RELIGIOUS-MYSTICAL SYMBOLS AND ITS STUDY IN MODERN HISTORIOGRAPHY - Elyor Alimkulov (Western European Studies, 2025)
This article examines the scientific works carried out by foreign researchers, as well as by encyclopedic Eastern scholars, who have conducted research on religious-mystical symbols. In particular, the meaning and essence of symbols are thoroughly explained with practical examples in the rare works of our great scholars such as Abu Nasr Farabi, Abu Rayhan Beruni, Al-Khwarizmi, Shahristani, Abu Ali ibn Sina, and Yusuf Khos Khajib. It also reveals the special importance of Western scholars' research on religious-mystical symbols in the historical and theoretical study of the topic. This includes studies by the Belgian political scientist E.G. d’Alviella, American philosopher Charles Peirce, Swiss linguist Ferdinand de Saussure, American philosopher Charles Morris, German philosopher Hegel, English ethnologist and religious scholar E. Taylor, and other scholars who have explored various aspects of symbols.
Keywords: God; courage; chastity